Produzir e ver o audiovisual na cibercultura: novos hábitos na contemporaneidade - Wagner Rodrigues Miranda (2017)
The advent of digital technologies ends up transforming the audiovisual experience, promoting a certain democratization of the means of production and access to content. Based on a brief historical panorama of the evolution of digital technologies, and on the concepts of convergence and participatory culture, this work proposes an analysis of the habits that are born or are enhanced by the advent of cyberspace. We investigate the practices of viewers, who have become more active and self-organizing, even participating in the creation and circulation of new content, and see how producers use the resources available to adapt to the new context.